Four new tydeid species from Iran (Acari: Prostigmata) - Khanjani, M.; Ueckermann, E. A. (Zootaxa, 2003)
Four new Iranian species namely Tydeus kabutarahangensis n. sp., T.caryae n. sp., Lorryia navidi n. sp. and L. vianensis n. sp. are described and illustrated. Tydeus momeni nom. nov. is proposed for Orthotydeus longisetosus El-Bagoury & Momen, 1988, a junior homonym of Tydeus longisetosus Kuznetzov & Zapletina, 1972.